Throwing a Bone to the Watchdog - Elliott, Carl (The Hastings Center report, 2001)
Bioethics is now taken seriously. Is there a danger of its being taken in or taken over? Might it be influenced in other ways, less visible and less easily avoided? As private corporations and bioethicists build relationships with each other, bioethicists must ask themselves about the opportunities, the constraints, and the subtle shifts in attitude and focus that such ties might create.